Visões das gerências da auditoriainterna da Petrobras sobre a sua estratégia de atuação em facedas práticas de mercado e da nova modelagem organizacional da companhia - Figueredo, Pedro Gauziski de Araujo (2002)
The purpose of this study is to identify the strategic vision of the Internal Audit Department of Petrel Brasileiro S.A. PETROBRAS, in comparison with the audit function's proposals and practices in competitive organizations and their reality. It also aims at the verification of the possible solutions, within Petrobras itself, so as to constantly add value to the business and to the shareholders. With this in mind, a research was carried out, contemplating the conceptual proposals and market practices related to auditing and to the current diagnosis and the organizational model of Petrobras, so as to choose elements for comparison and analysis of such vision. The results of this research pointed in the direction of questioning the organizational value of the internal audit action, concluding that it will only be possible to continuously attain such value by means of a permanent coordination with the organization's strategic level. This is especially true if the audit action participates effectively in the process of Corporate Governance, in defining the risks, the internal control system and the measurement of corporate performance, as related to the development of the strategic plan. However, any action along these lines is still heavily impacted and limited by several aspects of culture and relationship of the organizational power as well as by the beliefs of the organization and of the body of auditors. The involvement of the auditors as employees was also considered relevant in the auditing process, by means of the participation of the audited entities in self assessment2. This procedure is still not sufficiently guaranteed by successful experiments in major organizations, considering that there is not a clear demonstration of the effective benefits of adopting this practice, as ompared to the central control, seldom shared but strongly monitored by integrated information systems. Finally, this research points to the need to renew the concept of the formation and role of the auditors in modern competitive organizations, in the face of information technology and of automation of the instrument controls of the business. Therefore, one may conclude that the trend will be toward an action aiming at the revision of formal internal control matrixes, as they are established in such systems. On the other hand, the majority of audit human resources will be increasingly deployed to the evaluation of risk and control, as related to relevant events of a more abstract nature, as in the case of those connected with the uncontrollable factors of the external environment.